PROPOSING INNOVATIVE LEARNING WITH ACTIVE LEARNING IN THE CLASSROOM - Syamsudarni Syamsudarni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2013)
Research consistently has shown that traditional lecture methods, in which teachers/lecturers talk and students listen, dominate college and university classrooms. It is therefore important to know the nature of active learning, the empirical research on its use, the common obstacles and barriers that give rise to faculty members' resistance to interactive instructional techniques, and how faculty, faculty developers, administrators, and educational researchers can make real the promise of active learning. Instead of some examples of active learning are provided below, cooperative learning technique is the main focus as one of technique that the writers exposed. To conclude, the active learning is an alternative teaching to increase the quality of graduates. The use of active learning approach can increase the quality of teaching and learning.